2010
DOI: 10.1590/s0102-09352010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Células-tronco mononucleares autólogas e proteína óssea morfogenética na cicatrização de defeitos tibiais experimentalmente induzidos em cães

Abstract: RESUMOAvaliou-se a utilização de células-tronco mononucleares (CTM) na cicatrização de defeito ósseo experimental como alternativa aos métodos convencionais, analisando-se o tempo de evolução cicatricial e a presença dessas células no tecido neoformado. Foram utilizados 18 cães, separados em três grupos (G) de seis, e de cada animal foram colhidas células da medula óssea (MO), contadas e analisadas para morfometria, por meio da contagem manual e mielograma. Um defeito ósseo tibial foi então criado cirurgicamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 11 publications
2
14
0
9
Order By: Relevance
“…This biomaterial was sought because it did not trigger a local inflammatory response, whose degradation time does not interfere in the bone repair process and presents mechanical properties adequate for application in bone failures, as previously described in contemporary studies [23][24][25][26] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…This biomaterial was sought because it did not trigger a local inflammatory response, whose degradation time does not interfere in the bone repair process and presents mechanical properties adequate for application in bone failures, as previously described in contemporary studies [23][24][25][26] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bone marrow stem cell applied in the canine veterinary clinics¹ Ingrid S. Gomes², Vanessa C. de Oliveira 3 to their origin such as, embryonic or adult (Oliveira 2008, Santos et al 2013. Additionally, several studies demonstrated, the regenerative function of these cells in damaged tissues (Narazaki & Cristante 2011, Ryu et al 2012, Bittencourt et al 2016, Stolfi et al 2016.…”
Section: Topic Of General Interestmentioning
confidence: 99%
“…Adult stem cells can be isolated from various specialized tissues such as adipose tissue, bone marrow, tendon and cartilage (Colomé et al 2008, Oliveira et al 2010, Santos et al 2013. Consequently, the bone marrow stem cell (BMSC), from all the other tissues that have stem cells in Fig.1.…”
Section: Topic Of General Interestmentioning
confidence: 99%
See 2 more Smart Citations